Utility of Complete Mitochondrial Genomes in Phylogenetic Classification of the Species of Anopheles (Culicidae: Anophelinae) - Taghi Ghassemi-Khademi; Mohammad Ali Oshaghi; Hassan Vatandoost; Seyed Massoud Madjdzadeh; Mohammad Amin Gorouhi (Tehran University of Medical Sciences, 2021)
Background: Among the blood-sucking insects, Anopheles mosquitoes have a very special position, because they transmit parasites of the genus Plasmodium, which cause malaria as one of the main vector-borne disease worldwide. The aim of this review study was to evaluate utility of complete mitochondrial genomes in phylogenetic classification of the species of Anopheles. Methods: The complete mitochondrial genome sequences belonging to 28 species of the genus Anopheles (n=32) were downloaded from NCBI. The phylogenetic trees were constructed using the ML, NJ, ME, and Bayesian inference methods. Results: In general, the results of the present survey revealed that the complete mitochondrial genomes act very accurately in recognition of the taxonomic and phylogenetic status of these species and provide a higher level of support than those based on individual or partial mitochondrial genes so that by using them, we can meticulously reconstruct and modify Anopheles classification. Conclusion: Understanding the taxonomic position of Anopheles, can be a very effective step in better planning for controlling these malaria vectors in the world and will improve our knowledge of their evolutionary biology.